(RE-)INTRODUCING N CHABANI MANGANYI - Hayes, Grahame (PINS-Psychology in Society, 2025)
The reprinting of Manganyi’s (1997) work, “The violent reverie”, is introduced through a contextualisation of the social relations that form the structural and material foundations of violence. To this end the ideas of Zizek on the symbolic and systemic dimensions of violence, and Badiou’s account of the “violent history” of democracy, are briefly discussed. The central argument of Manganyi’s argument is adumbrated, namely, that the violent reverie has the potential to offer a creative expression to the alienation and anguish of the subordinated racial (black) subject. The article concludes with a brief introduction to Manganyi’s impressive oeuvre that incorporates work on psychology, biography, and contemporary politics.